Measuring cardiorespiratory variables on small tadpoles using a non-invasive methodology - Longhini, Leonardo Sambini [UNESP]; De Almeida Prado, Cynthia P. [UNESP]; Bícego, Kênia C. [UNESP]; Zena, Lucas A.; Gargaglioni, Luciane H. [UNESP] (My University, 2019)
Introduction: Cardiorespiratory studies in tadpols species are scarce, reflecting challenges of using invasive tools, for measuring heart rate (fH) and breathing frequency (fB) by means of implanting electrodes, cannulae, and others, especially in the case of long-term measurements. This study attempted to improve techniques previously used by Longhini and coworkers (2017) on measuring cardiorespiratory parameters non-invasively in bullfrog tadpoles in a much smaller anuran tadpole specie, Boana albopunctaca (Anura: Hylidae) from the Savannah-like Cerrado. This specie occurs in the central, southern and southeastern regions of Brazil in an area where deforestation levels are high. Objective: To determine the resting values for fH and fB of tadpoles (stage 26 from Gosner, 1960) B. albopunctata at 25°C using a non-invasive methodology. Additionally, we determined the Maximum Critical Temperature (CTmax) by exposing tadpoles to a heating ramp (1°C/4min). Material and Methods: Pre-metamorphic tadpoles (N=11) of Boana albopunctata were collected (SISBIO: 621361) in the Cerrado biome, in Minas Gerais state (20º 14' 43 S; 46º 21' 57 O), and maintained in the lab in aquariums at 25°C. The cardiorespiratory parameters, fH and fB, were obtained by a non-invasive electrocardiogram (ECG) and surface electromyogram (EMG) method, respectively. After baseline measurement, animals were handled in order to administer an intraperitoneal injection of Ringer solution (vehicle) to verify the influence of the injections on the basal cardiorespiratory parameters, which were recorded for an additional hour. For that, we used a thin dental needle (30 gauge) connected by a polyethylene tube (PE10, Clay Adams) to a Hamilton syringe (5 μl). The CTmax, the temperature at which animals lose the ability to escape from conditions that may ultimately lead to death, was determined by exposing tadpoles acclimatized at two different temperatures (15 and 25°C) to a constant heating rate of 1°C/4min. When the animals began to present loss of equilibrium, we stimulated them with a glass rod, and considered the CTmax when tadpoles were motionless after five consecutive taps. Immediately after assessing CTmax, we transferred tadpoles to plastic cups with water at ambient temperature (25°C). We validated the CTmax for individuals that remained alive for at least 24 h after the test. The data obtained were expressed as mean ± s. e. m. Results: At 25°C, baseline values for fH and fB were 104.6 ± 20.0 and 85.94 ± 18.9, respectively. Cardiorespiratory parameters were not significantly affected by the intraperitoneal Ringer solution injection: fH (beats.min−1): 103.2 ± 15.6 and fB (movements.min−1): 85.3 ± 16.1. Animals’ acclimatized at 20°C exhibited CTmax of 35.88 ± 1.58°C compared to those acclimatized at 30°C, with a CTmax of 39.57 ± 0.49°C. Conclusion: According to our preliminary results, we confirm that the non-invasive methodology adapted for larger tadpoles (e.g Bullfrog; size: ~9 cm) can be improved for measuring cardiorespiratory parameters non-invasively in small tadpoles (size: ~4 cm).After one hour from intraperitoneal ringer injection, fH and fB returned to their baseline values. Furthermore, animals acclimated to the higher temperature (30°C) showed greater thermal tolerance during a heating rate protocol.
Keywords: Boana albopunctaca; Bucal movements frequency; Heart rate; Savannah-like Cerrado